Case Report: Neuropsychiatric improvement after treatment of pelvic venous disorder in a multisyndromic patient - Smith, Steven J.; Sichlau, Michael J.; Rowe, Peter C.; Knight, Dacre R. T.; Chen, Brenda; Smith, B. Holly; Sichlau, Isabel C. (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveVenous Origin Chronic Pelvic Pain (VO-CPP) causes pelvic pain in women, and is associated with other dysautonomia syndromes such as postural orthostasis and tachycardia syndrome (POTS), chronic fatigue, interstitial cystitis, and fibromyalgia. These conditions have been shown to have associations with Ehlers–Danlos syndrome, migraine headache, irritable bowel syndrome, and brain fog. In this study, a multisyndromic patient was treated for VO-CPP. Pelvic pain, dysautonomia, and neuropsychiatric scores were tracked in this patient.MethodsIn a multisyndromic patient with VO-CPP, abnormal venous pooling was treated with endovascular stenting and sclerotherapy. Neuropsychiatric testing was performed before and after intervention.ResultsAlong with improvement in scores for pelvic pain, POTS, interstitial cystitis, and migraines, repeat neuropsychiatric testing showed improvement in Memory Functioning Recall and Depression Inventory. The patient’s previous disability status was removed.ConclusionsThe patient's response to endovascular treatment supports a unifying concept of diminished venous return as a contributor to multiple syndromes that may be linked to a single phenotype.